CHARACTERIZING COVID-19–RELATED RETINAL VASCULAR OCCLUSIONS: A Case Series and Review of the Literature. Issue 3 (March 2022) - Fonollosa, Alex; Hernández-Rodríguez, José; Cuadros, Carlos; Giralt, Lena; Sacristán, Cristina; Artaraz, Joseba; Pelegrín, Laura; Olate-Pérez, Álvaro; Romero, Rosa; Pastor-Idoate, Salvador; Sobas Bsc, Eva María; Fernández-Fidalgo, Sonia; et al.
Abstract : In patients with coronavirus disease-19, retinal vascular occlusions may develop synchronically or several weeks after the initial coronavirus disease-19 manifestations and tend to affect individuals younger than 60 years. Retinal vein occlusions are the most frequent vascular occlusive disease, and they are usually associated with good prognosis. Abstract : Purpose: To describe clinical and ophthalmologic features and outcomes of patients with coronavirus disease-19 with retinal vascular occlusions. Methods: Retrospective multicenter case series and PubMed review of cases reported from March 2020 to September 2021. Outcome measures are as follows: type of occlusion, treatments, best-corrected visual acuity, and central macular thickness on optical coherence tomography. Results: Thirty-nine patients were identified. Fifteen patients with a median age of 39 (30–67) years were included in the multicenter study. Vascular occlusions included central retinal vein occlusion (12 eyes), branch retinal vein occlusion (4 eyes), and central retinal artery occlusion (2 eyes). Three cases were bilateral. Baseline best-corrected visual acuity was 20/45 (no light perception-20/20). Baseline central macular thickness was 348.64 (±83) μ m. Nine eyes received anti–vascular endothelial growth factor agents, dexamethasone intravitreal implant, or both. Final best-corrected visual acuity was 20/25 (no light perception-20/20), and central macular thickness was 273.7 ± 68 μ m (follow-up of 19.6 ± 6 weeks). Among the 24 cases from the literature review, retinal vein occlusion was the predominant lesion. Clinical characteristics and outcomes were similar to those found in our series. Conclusion: Coronavirus disease-19–associated retinal vascular occlusions tend to occur in individuals younger than 60 years. Retinal vein occlusion is the most frequent occlusive event, and outcomes are favorable in most cases.